Islamic Civilization and Thought During The Umayyad Dynasty in The East (Damascus) and West (Andalusia) - Muhammad Roisul Muttaqin; Izah Ulya Qadam; Ryan Muhammad Ridwan (Journal Analytica Islamica, 2023)
The development of Islam after the Khulafaurrasyidin era was continued by the Umayyad dynasty. During its journey, the Umayyad dynasty was divided into two periods, namely the Eastern Umayyad dynasty (Damascus), now known as Syria, and the Western Umayyad dynasty (Andalusia), now known as Spain. This research aims to explain Islamic civilization and thought during the Umayyad dynasty. This research uses descriptive qualitative methods with literature. This research data obtained from the literature comes from books and journals related to the research title. This research resulted in a reign of 90 years in Damascus and 280 years in Andalusia. The development of science in Damascus was concentrated on the science of tafsir, hadith, qiro'at, nahwu, hadith and language, while from an economic perspective during the Umayyad dynasty there was also a significant increase. significant and also the factors that caused the decline of the Umayyad dynasty in Andalusia. Perkembangan agama islam setelah masa khulafaurrasyidin dilanjutkan oleh dinasti umayyah. Dalam perjalanannya dinasti umayyah dibagi menjadi dua periode, yakni dinasti umayyah timur (damaskus) sekarang dikenal dengan negara siria dan dinasti umayyah barat (andalusia) yang sekarang dikenal dengan negara spanyol. Penelitian kali ini bermaksud untuk menjelaskan mengenai peradaban serta pemikiran islam pada masa dinasti umayyah. Penelitian ini menggunakan metode kualitatif deskriptif dengan kepustakaan. Data penelitian ini yang diperoleh dengan kepustakaan berasal dari buku-buku maupun jurnal yang terkait dengan judul penelitian. Penelitian ini menghasilkan masa pemerintahan 90 tahun di damaskus dan 280 tahun di andalusia, perkembangan ilmu pengetahuan di damaskus terkonsentrasikan pada ilmu tafsir, hadits, qiro'at, nahwu, hadits dan bahasa, sedangkan dari segi ekonomi pada masa dinasti umayyah juga telah mengalami peningkatan yang signifikan dan juga faktor-faktor yang menjadi kemunduran pada dinasti umayyah di andalusia.